2013
DOI: 10.1136/ejhpharm-2012-000113
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for development and pre-implementation validation of effective clinical decision support

Abstract: Objective Well-designed clinical decision support systems (CDSS) can reduce the problem of alert fatigue by generating patient-specific alerts. This paper describes a strategy for the development and pre-implementation validation of specific and relevant clinical rules in order to reduce alert fatigue. Methods A four-step development and validation strategy of clinical rules is presented. As an example, from March to September 2006 the ‘lithium therapy rule’ was developed with this strategy based on the Plan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 21 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…Key to preventing alert fatigue in active CDSS is structured development and validation of clinical rules. Much has been published on the validation of these clinical rules focusing on providing maximal clinical relevance of the recommendations outputted by the CDSS [47,[57][58][59].…”
Section: Development and Validation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Key to preventing alert fatigue in active CDSS is structured development and validation of clinical rules. Much has been published on the validation of these clinical rules focusing on providing maximal clinical relevance of the recommendations outputted by the CDSS [47,[57][58][59].…”
Section: Development and Validation Strategymentioning
confidence: 99%
“…Below we describe a four-step strategy to develop and implement clinical rules, which we ourselves use as part of development [57,61].…”
Section: Strategy For Development and Validation Of Clinical Rulesmentioning
confidence: 99%
“…In 2008, the clinical rule for ´Opioid-Laxative Use´ was developed according to a strategy designed in our hospital. This strategy is based on the Plan-Do-Check-Act cycle and includes an expert team that optimises the quality and clinical relevance of clinical rules [10]. The 'Opioid-Laxative Use' rule was specifically selected for development based on a national study that identified high-risk patients with medication-related problems leading to hospital admission [15].…”
Section: Clinical Rule 'Opioid-laxative Use'mentioning
confidence: 99%
“…Reducing or avoiding opioid-induced constipation (OIC) is an important objective for improving the management of patients with chronic pain. Opioid dose reduction or discontinuation of opioid Retrospective research in the Catharina Hospital in Eindhoven in 2008 showed that co-prescription of a laxative was omitted at the start of therapy in 67% of clinical patients receiving opioids [9,10]. A study by Bouvy et al showed that pharmacy intervention can lead to better opioid and laxative combination therapy in the community setting [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation